Pola Pengajaran Kesantunan Berbahasa Anak Di Lingkungan Keluarga - Elvita Yenni; Yusriati Yusriati; Ambar Wulan Sari (JURNAL TARBIYAH, 2018)
This research was about parents way in teaching politeness in their environment. The objectives of this research were (1) to examine parents’ perception about teaching language politeness to their children in a family environment;(2) to describe what patterns are implemented by parents in teaching language politeness to the children;(3) to find out the forms of language politeness taught to the children and  (4) to describe the obstacles encountered by parents when they taught their children language politeness.Descriptive qualitative design was used  in this research. The data were obtained   by doing the interview and observation to the objects of research. The result revealed that all parents agreed about teaching language politeness to their children in a familay environment based on some reasons.First, famliy is the first place for children to learn about politeness. Second, teaching language politeness to children is one way to maintain our culture and third, teaching language politeness to the children can make them far from the dispute. Teaching language politeness to the children must be done  through refraction, instruction, control, and modelling.